Localized surface plasmon resonance based bowtie nanoantenna for optical biodetection - Kalam, Fateen Bin; Biswas, Sushmita; Shakib, Fatema (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.